Intelligence among the Students of Jawahar Navodaya Vidyalayas and Kendriya Vidyalayas - N.C., Kiran; Murthy, C.G.Venkatesha (JOURNAL OF INDIAN EDUCATION, 2018)
In the present study, the researchers have attempted to assess the intelligence among 770 Class VIII students in all. Of these, 320 are from Jawahar Navodaya Vidyalayas (JNVs) and 450 from Kendriya Vidyalayas (KVs). There was a significant difference between the students of JNVs and KVs on intelligence in favour of JNV students. Among the students of JNVs and KVs, the boys and girls do not differ significantly on intelligence.